Bank Risk Taking Behaviour in Malaysia: Role of Board and Ownership Structure - Linda Loh; Chan Sok-Gee (Asian Academy of Management Journal of Accounting and Finance, 2017)
This paper examines the role of board structure and ownership concentration on bank risk-taking of public listed commercial banks in Malaysia from 2001 to 2012. The study focuses on the bank-risk taking behaviour after the major bank consolidation in Malaysia in year 2000. Using two-market model to estimate the risk of the commercial banks in Malaysia, the results suggest that higher ownership concentration and larger board size resulted in higher bank risk-taking of the listed commercial banks in Malaysia. Given that the board structure is an important element of bank risk-taking, regulators should continue to enhance the monitoring of banks (where board size is large and ownership concentration is high) to control the banks’ potential for excessive risk taking.